Composites based on modified clay assembled Rh(III)–heteropolymolybdates as catalysts in the liquid-phase hydrogenation of cinnamaldehyde - Bertolini, Guillermo Ramón (2016)
New composites based on the [RhMo6O24H6]3− (RhMo6) heteropolyanion supported on pillared (PILC), heterostructured (PCH) and functionalized(PILC-F) and (PCH-F) systems based on clays were prepared, characterized and tested as catalysts in the liquid-phase hydrogenation of cinnamaldehyde. The original phases and supported systems were characterized using several techniques such as powder X-ray diffraction (XRD), scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM–EDS), Raman microprobe studies, X-ray photoelectron spectroscopy (XPS), thermogravimetry and differential thermal analyses (TG-DSC), temperature programmed reduction (TPR), and textural analysis (BET method), which confirmed their functionalization, physicochemical modification and the nature of Mo adsorbed species. Active acidic, basic and redox sites were determined by temperature programmed surface reaction (TPSR). Mo loading reached 7 wt% for the system RhMo6/PCH-F and 3 wt% for the system RhMo6/PILC-F, while unfunctionalized clay systems showed a value of 1 wt% of Mo. The catalytic performance showed that PCH-based composites were the most active and reached up to 56% conversion at 360 min of reaction when tested in liquid-phase cinnamaldehyde hydrogenation. The selectivity for all the systems was mainly toward hydrocinnamic aldehyde (HCAL) and reached 77% for the RhMo6/PCH-F catalyst at 25% conversion.